Culturally Contextualized Artificial Intelligence-Based Video Design to Improve Indonesian Speaking Skills - Maya Oktora; Yuni Khairina; Suci Pujiastuti; Zulfidar (Journal of Education Reseach and Evaluation, 2025)
In the context of Indonesian language learning, particularly speaking skills, AI-based innovations can provide solutions to persistent challenges such as low student motivation, limited classroom time for speaking practice, and the lack of instructional media capable of delivering rapid and personalized feedback. This study aims to develop a learning medium that addresses key challenges faced by beginner learners, including difficulties in pronouncing unfamiliar phonemes, constructing grammatically appropriate sentences, and building confidence in oral communication. This study employed a development research approach using the ADDIE instructional design model. A mixed-methods approach with a sequential explanatory design was adopted, involving five international students. Data were collected through pre- and post-tests, classroom observations, and semi-structured interviews. Data analysis was conducted using qualitative and quantitative descriptive techniques. The findings demonstrate significant improvements in participants’ pronunciation, sentence construction, and confidence in speaking Indonesian. AI-based videos integrated with cultural contexts functioned as effective supplementary media in foreign language learning by providing linguistic feedback and cultural exposure. It can be concluded that the integration of such media enhances learner engagement and supports the development of oral communication skills, while further exploration of interactive features is recommended to encourage spontaneous communication. The implications of this study indicate that designing culturally contextualized AI-based videos can represent a significant breakthrough in Indonesian language instruction, particularly in developing speaking skills.